Experimental Investigation of Air-to-Kapok Oil Ratio Effects on Flame Height and Morphology in a Bunsen Burner - Bayu Pranoto; Nicky Suwandhy Widhi Supriyanto; Chandra Gunawan; Supa Kusuma Aji; Muhammad Arif Nur Huda (Universitas Islam Raden Rahmat, Malang, 2025)
The growing global demand for energy highlights the limitations of fossil fuel resources. This makes innovation in alternative energy development crucial, and one promising avenue is the use of vegetable oils like kapok oil. Kapok oil has a complex chemical composition, composed of various triglycerides of fatty acids and glycerol, where each fatty acid component contributes unique combustion characteristics. The interaction of the complexity of this content as a whole affects the flame pattern of kapok oil. Furthermore, the air-fuel mixture ratio (AFR) plays a significant role in determining the characteristics of the resulting flame. Therefore, this study aims to explore in depth the effect of AFR variations on the combustion characteristics of kapok oil. Experiments were conducted by burning a mixture of kapok oil vapor and air on a burner with controlled AFR settings. The results showed that the variation of AFR significantly changed the flame height and morphology. Flame height initially increased with increasing AFR (from 1.34 cm at AFR 0.143:1 to 4.429 cm at AFR 1.526:1) before decreasing (to 0.264 cm at AFR 4.011:1) until it reached the lift-off condition and went out.